Multiplexing and De multiplexing using Visual Basic Program - AL-Mafrji, Ahmad A. Mohammed (Discoveries in Agriculture and Food Sciences, 2018)
The strategy of the global telecommunications companies always provide the best services to users is the high speed in the transfer of reliable data and a large amount of data (calls) with the least effort and cost. This study focuses on the use of simulations for the implementation of Multiplexing technique and DE Multiplexing technique through programming using Visual Basic language. The simulation helps to give an easy and clear idea of how Multiplexing technique and DE Multiplexing technique work. The system was created and implemented using the Visual Basic 8.0.